SOIL MULCHING AND DEFICIT IRRIGATION WITH WASTEWATER IN THE QUALITY OF ITALIAN ZUCCHINI - Sena, Carolina Carvalho Rocha; Ferreira, Anamaria Achtschin; Evangelista, Zeuxis Rosa; Araujo, Kari Katiele Souza (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
Conscious agricultural management, which aims to conserve natural resources, has been the target of contemporary agriculture. In this context, the reuse of water in deficit water depth in agricultural irrigation becomes a viable technique, and this work aimed to evaluate the effect of different irrigation depths with wastewater and soil mulching on the microbiological and postharvest characteristics of the Italian zucchini. The experiment was conducted in the field conditions with a randomized block design in a split-plot arrangement. Four irrigation depths (100%, 85%, 70%, and 55% of the estimated ETc from the Class A Evaporation Pan) and three types of soil mulching (rice husk, double-sided black and white polyethylene film, and uncovered soil) were analyzed. Texture, titratable acidity (TA), soluble solids content (ºBrix), pH, and the ºBrix:TA ratio of the Italian zucchini were analyzed, besides the microbiological analysis. The irrigation depth or soil mulching did not influence the pH of the Italian zucchini. The uncovered soil promoted higher titratable acidity to the Italian zucchini. The texture of the fruit, the soluble solids, and the ºBrix:TA ratio was influenced by the types of soil mulching and irrigation depths. The use of wastewater for drip irrigation reduces the effects of the microbial load on the crop.